ATHENA (GOG-3020/ENGOT-ov45): a randomized, phase III trial to evaluate rucaparib as monotherapy (ATHENA–MONO) and rucaparib in combination with nivolumab (ATHENA–COMBO) as maintenance treatment following frontline platinum-based chemotherapy in ovarian cancer - Monk, Bradley J; Coleman, Robert L; Fujiwara, Keiichi; Wilson, Michelle K; Oza, Amit M; Oaknin, Ana; O’Malley, David M; Lorusso, Domenica; Westin, Shannon N; Safra, Tamar; Herzog, Thomas J; Marmé, Frederik; et al. (International journal of gynecological cancer, 2021)
BackgroundThe optimal treatment strategy for women with newly diagnosed ovarian cancer has yet to be determined. Poly(ADP-ribose) polymerase (PARP) inhibitors have demonstrated substantial improvement in progression-free survival as monotherapy maintenance treatment in the frontline setting versus active surveillance. Furthermore, preclinical and early clinical studies have shown that PARP inhibitors and immune checkpoint inhibitors have synergistic antitumor activity and may provide an additional therapeutic option for patients in this population.Primary ObjectivesIn women with newly diagnosed ovarian, fallopian tube, or peritoneal cancer, we wish to assess the efficacy of frontline maintenance treatment with the PARP inhibitor rucaparib versus placebo following response to platinum-based chemotherapy (ATHENA–MONO), and to assess the combination of rucaparib plus nivolumab (a programmed death receptor 1 (PD-1)–blocking monoclonal antibody) versus rucaparib alone (ATHENA–COMBO).Study Hypothesis(1) Maintenance therapy with rucaparib monotherapy may extend progression-free survival following standard treatment for ovarian cancer in the frontline setting. (2) The combination of nivolumab plus rucaparib may extend progression-free survival following standard treatment for ovarian cancer in the frontline setting compared with rucaparib alone.Trial DesignATHENA is an international, randomized, double-blind, phase III trial consisting of two independent comparisons (ATHENA–MONO and ATHENA–COMBO) in patients with newly diagnosed platinum-sensitive ovarian cancer. Patients are randomized 4:4:1:1 to the following: oral rucaparib+ intravenous nivolumab (arm A); oral rucaparib + intravenous placebo (arm B); oral placebo+ intravenous nivolumab (arm C); and oral placebo + intravenous placebo (arm D). The starting dose of rucaparib is 600 mg orally twice a day and nivolumab 480 mg intravenously every 4 weeks. ATHENA–MONO compares arm B with arm D to evaluate rucaparib monotherapy versus placebo, and ATHENA–COMBO evaluates arm A versus arm B to investigate the effects of rucaparib and nivolumab in combination versus rucaparib monotherapy. ATHENA–MONO and ATHENA–COMBO share a common treatment arm (arm B) but each comparison is independently powered.Major Inclusion/Exclusion CriteriaPatients ≥18 years of age with newly diagnosed advanced, high-grade epithelial ovarian, primary peritoneal, or fallopian tube cancer who have achieved a response after completion of cytoreductive surgery and initial platinum-based chemotherapy are enrolled. No other prior treatment for ovarian cancer, other than the frontline platinum regimen, is permitted.Primary EndpointThe primary endpoint is investigator-assessed progression-free survival by Response Evaluation Criteria in Solid Tumors v1.1.Sample SizeApproximately 1000 patients have been enrolled and randomized.Estimated Dates for Completing Accrual and Presenting ResultsThe trial completed accrual in 2020. While dependent on event rates, primary results of ATHENA–MONO are anticipated in early 2022 and results of ATHENA–COMBO are anticipated to mature at a later date.Trial RegistrationThis trial is registered at clinicaltrials.gov (NCT03522246).